Late snowfall and blizzards in Moldavia. April 2017 summary case of study - R. MANTA; L. SFÎCĂ; A. TIȘCOVSCHI; D. CONSTANTIN; V. MĂNOIU; C. RADU (Aerul şi Apa: Componente ale Mediului, 2018)
While these are normal phenomena for Romania’s geographical position, heavy snows and intense blizzards can have severely negative effects, especially when they occur unseasonably, before or after the typical period. The blizzard recorded on 19-20 April 2017 was particularly violent and one of the latest blizzard events in the history of meteorological observations. In comparison, the last significant late winter event, albeit lower in intensity, was recorded on 15-16 April 1996. However, the blizzard formation mechanism in the month of April in eastern regions is relatively similar. The presence of a high-pressure zone in the central-western European region led, in both cases, to fast large-scale penetrations of arctic air from high latitudes towards areas with high cyclogenetic potential in the Mediterranean Sea basin. Thus, the depressions of Mediterranean origin, which formed in the Genova Gulf area, advanced towards the Black Sea basin via trans-Balkan trajectories, where they regenerated and resulted in strong windintensification and abundant precipitation in the Moldavian region. With regard to the event this study analyses, the high thermobaric contrast and the presence of a sufficiently cold air mass favored, during the night between the 19th and the 20th of April, the occurrence of a strong blizzard event in Moldavia, following abundant wet snowfall during the day. At several meteorological stations across Moldavia and Transylvania, as well as in mountainous areas, the maximum winter snow layer thickness was exceeded on the 20th and 21st of April.